Clinicopathological profile of rickettsial fever in tertiary healthcare centre: a prospective case study - K., Mallesh; Sabapathy, Sarala; Patil, Rashmi; Shetty, Niharika (International Journal of Contemporary Pediatrics, 2020)
Background: Rickettsia are obligate intracellular proteobacteria spread by eukaryotic vectors like ticks, mites, fleas and lice. Rickettsial infections are generally incapacitating and difficult to diagnose; Case fatality rates up to 45 percent is seen in cases with multiple organ dysfunction. The disease continues to be under diagnosed and treated. Objective of this study was to study the clinicopathological profile and outcome of children admitted with rickettsial fever. To study the correlation between Rathi-Goodman-Aghai score and Weil-Felix test. To study the response of rickettsial fever to Doxycycline. Methods: This study is a prospective observational study conducted from December 2017 to April 2019 at a tertiary health care center in South India, involving patients admitted between 2 months to 18 years of age with a diagnosis of Rickettsial fever. Clinical data and investigations were collected and analysed. The response to doxycycline was recorded. Results: Total of 49 patients were enrolled in the study. Most common age group affected was between 1 to 5 years accounting for 32.7% of the cases. 78% of the patients hailed from rural background. Most common presentation being fever, present in 100% of the cases. 81.6% of patients had significant Rathi-Goodman-Aghai score of >14. Weil felix showed significant titres (1:80) in 97.9% out of which serology suggestive of scrub typhus was found in 79.6% patients. There was no statistical significance between rickettsial score and Weil-Felix test (p value= 0.736). 26.5% of the cases required respiratory support and 2% cases required dialysis. 10.2% cases succumbed and 89.8% cases improved. Conclusions: Rickettsial infection is re-emerging with propensity for life threatening complications. There is no statistical significant correlation between Rickettsial score and Weil Felix test. Early treatment has better outcome.